Description of Microbiological Food Sample Check in Dr. Soetomo Hospital Surabaya - Miftakhul Nikmah (Universitas Airlangga, 2018)
The outbreak of food poisoning in 2011 which has been collected by BPOM RI recorded that there was 128 cases. As many as 18,144 people was exposed by contaminated food. There was 84 cases of food poisoning caused by Escherichia coli bacteria in 2013, while there was 47 cases in 2014. There were 60 incidences with 1106 cases of food poisoning in East Java during 2012. In Surabaya there was 93 cases of food poisoning during 2015. The purpose of this study was to describe food safety in RSUD Dr. Soetomo Surabaya. The research type was descriptive observational using secondary data from environmental sanitation installation inspection such as the result of food sample, dinnerware, and cookware examination. Data was compared to the regulation which was used by RSUD Dr. Soetomo Surabaya. The food samples, dinnerware, and cookware examination were done by BBTKLPP Surabaya four times a year. The results of the examination of the dinnerware sample in IRNA Palem 2 was 0,39 kol/cm3 and IRNA Cendana was 15 kol/cm3, there were not fulfilled the requirements. The conclusion of this research was the number of germs in the examination of the dinnerware was not in fulfilled the requirements in the regulation of the Health Minister No. 1096 of 2011 about Sanitation Hygiene of Catering Service. It is recommended that the nutrition installation to train to kitchenware washer and the IRNA kitchen managers about how to wash correctly and to pay attention to the washing way in order to minimize the contamination of Escherichia coli bacteria.